SISTEM INFORMASI MANAJEMEN KEUANGAN BERBASIS WEB BENGKEL MOBIL CV. ANEKA BINTANG SERVICE - Mulyana, Wide; Ridhwan, Muhammad; Yen’s Sari, Cintiya Novitaras; Tobing, Ardyana Lumban; Padma Sitorus, Zoe Adesso (JURSIMA, 2022)
CV. Aneka Bintang Service, established in 1998, is a company operating in the automotive sector with over 12 employees. Currently, this workshop is facing challenges in business administration due to its reliance on an unstructured manual system. To improve operational effectiveness and efficiency, this research proposes the design of a web-based information system that includes data management and financial management. The system aims to facilitate business processes, reduce customer complaints, and optimize the management of customer data, customer transactions, and payment processes. The research methods used include needs analysis, UML design, system and database planning, and user interface design. With the implementation of this system, it is expected that there will be an increase in operational efficiency, more accurate transaction recording, and real-time cash flow monitoring, thereby making it easier for both the workshop and customers to conduct business activities.